Pilkada dan Pelayanan Kesehatan di Rumah Sakit Umum Daerah Kabupaten Kuantan Singingi - ADLIN ADLIN; ALI YUSRI (Universitas Sumatera Utara, 2016)
Kabupaten Kuantan Singingi is one area that participate in implementing simultaneous local elections in Indonesia in December 2015. The organization of local elections in other areas do not have an impact on health services in district hospitals (RSUD). However the reality in the District kuantanSingingi, the elections have resulted in interruption of health services.Since March 7, 2016 outpatients especially BPJS (Social Security Administrator) patients do not get health care.The results of this study showed that there are several factors that cause the cessationof health services in hospitals Kuantan Singingi. First, the political elite in the executive and the legislature is too busy with the activity of winning candidate in the local election;Second, the candidate who supported bye the incumbent was defeated. Then they do a lawsuit to the Mahkamah Konstitusi (Constitutional Court);Third, the Bupati (incumbent regent) and Team (Local Government Budget) is inaccurate and unwise when making budget planning. Including Health Care Budget;Fourth, the bureaucracy has been involved in practical politics. So that they do not carry out their duties and functions as a budget planner;Fifth, the execution time of the lovcal election at the same time with the drafting of the budget.This study is using behavorial approach and the method isqualitative. The data collection is using interviews.Keywords: Elections, Political Budget, Health Services.